Mathematical Critical Thinking Ability in terms of Student Learning Independence Character in SQ4R Learning Model with Project Assessment (Universitas Negeri Semarang, 2022)
The purpose of this research was to describe critical mathematical thinking in terms of the character of students learning independence. The method used in this research is mixed metholds using a concurrent embedded model. The population in this study were students of class XI MA Mu'allimat NU Kudus Academic Year 2018/2019. The data in this study were obtained by using a character questionnaire for independent learning, observation, mathematics critical thinking tests and interviews. The subjects in this study were based on the character category of student learning independence, namely the category of students with high, medium, and low student learning independence characteristics. The result of the research is that SQ4R learning with a project assessment is effective in improving students critical mathematical thinking and enhancing the character of students learning independence. Students who have high learning independence character and moderate learning independence will create excellent critical thinking skills. Students who have low learning independence are classified as good.